Responsibilities and education of hospital dietitians and nutritionist in the Greater Manila area - Amistoso, Annabelle Y.; Florencio, Cecilia A. (1975)
This is a study of the responsibilities and education of 154 dietitians and nutritionists in 42 hospitals in the Greater Manila area with a minimum bed capacity of 75 and licensed by the Bureau of Health and Medical Services of the Department of Health as of July 1973. The main objective of the study was to determine the perception of the dietitians and nutritionists of the adequacy of their educational preparation for their actual responsibilities. Data were obtained by meas of a questionnaire which was distributed and collected personally during the period of July to September 1974. Majority of the hospitals were located in Manila and Quezon City. Thirty-one were private and 11 were government,. Three to four hospitals had bed capacities of less than 100 or more than 999 while 35 were within the capacity range of 100-999. Forty percent of these hospitals did not have the minimum number of dietitians requires by Section 11 of Republic Act 2674. The respondents had 52 different job titles. Analysis of their respective responsibilities showed that most of them had similar responsibilities even if their job titles were different. In fact they can be classified into just five major job titles: chief dietitian; administrative dietitian; therapeutic dietitian; staff dietitian; and nutritionist. Of the 116 items of responsibility which respondents thought should be added to their actual responsibilities, two were significant. These were the responsibility of making ward rounds with the medical team and consulting or holding conferences with doctors and other members of the medical team. Not one of the 86 items of the responsibility which they believed should be removed from their actual responsibilities was significant. Findings of this study could serve as bases for strengthening the training of dietitians in both the undergraduate level and dietetic internship; for determining their additional training needs;l and for planning appropriate topics, for seminars, workshops, an conferences. They also point to the need to look into the following: standardization of job titles; formulation of recommended responsibilities for the different dietetic positions in the dietary department; and the provisions of Republic Act 2674 regarding the ration of the number of dietitians in relation to hospital size.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Dietitians; Hospitals -- Philippines -- Manila -- Food service